О родовой принадлежности аблефаридных ящериц (Reptilia, Sauria, Scincidae) фауны СССР - Еремченко, В.К.; Щербак, Н.H. (Вестник зоологии, 1980)
Revision of species which were earlier attributed to the Eurasiatic genus Ablepharus has showfi that A. alaicus, which clearly differs from all other species in nonaccreted eyelids, seven teeth on the premaxillary bones, palate structure, a larger otic foramen, the presence of the enlarged squamules on the antebrachium and tibia and in other pholidosis characters as well as in eggviviparity, belongs to the new genus Asymblepharus close to the ancestors of Scincella and Ablepharus genera.